A simple scheme for semi-recursive identification of Hammerstein system nonlinearity by Haar wavelets - Śliwiński, Przemysław; Hasiewicz, Zygmunt; Wachel, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
A simple semi-recursive routine for nonlinearity recovery in Hammerstein systems is proposed. The identification scheme is based on the Haar wavelet kernel and possesses a simple and compact form. The convergence of the algorithm is established and the asymptotic rate of convergence (independent of the input density smoothness) is shown for piecewise-Lipschitz nonlinearities. The numerical stability of the algorithm is verified. Simulation experiments for a small and moderate number of input-output data are presented and discussed to illustrate the applicability of the routine.
Keywords: Hammerstein systems; non-parametric recursive identification; Haar orthogonal expansion; convergence analysis; numerical stability